2008
DOI: 10.1017/s1368980007001413
|View full text |Cite
|
Sign up to set email alerts
|

The humanitarian emergency in Burundi: evaluation of the operational strategy for management of nutritional crisis

Abstract: Objective: To evaluate the impact and appropriateness of programmes for the management and treatment of severe malnutrition in emergency situations. Design: A central unified database was set up with all data and statistics provided by nutritional centres (NC) active in Burundi. Setting: The paper describes the case of Burundi as an example of the response of the humanitarian community to nutritional crisis. Subjects: Since 1999, more than one million (1 054 210) severely malnourished patients were treated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Rossi et al . demonstrated a mortality reduction (6/10 000 to 3.1–4.9/10 000) using selective feeding in a large population (more than 1 million participants), though the quality of evidence was very low . Preventive food supplementation and distribution reduced mortality in two studies of different quality.…”
Section: Resultsmentioning
confidence: 99%
“…Rossi et al . demonstrated a mortality reduction (6/10 000 to 3.1–4.9/10 000) using selective feeding in a large population (more than 1 million participants), though the quality of evidence was very low . Preventive food supplementation and distribution reduced mortality in two studies of different quality.…”
Section: Resultsmentioning
confidence: 99%
“…beans) are one of the main agricultural products (33) . These uncertainties should not deter further pursuit of alternative food-based solutions, including leaf fractionation, to nutritional problems among impoverished and vulnerable communities, particularly where local resilience might be needed in the face of endemic food insecurity and episodic civil instability (34,35) . In the meantime, our small study in a particularly vulnerable group has demonstrated that a leaf-derived food supplement could meet this need as effectively as a conventional milk-based supplement.…”
Section: Discussionmentioning
confidence: 99%
“…A national programme of therapeutic and supplementary feeding during a humanitarian emergency in Burundi seemingly failed to reduce the prevalence of wasting, perhaps because only 55% coverage was achieved [11]. Three different lines of evidence suggested that supplementary feeding programmes during a war in Guinea-Bissau prevented in increase in the prevalence of undernutrition [12].…”
Section: Discussionmentioning
confidence: 99%